Analysis of the Decrease in Compressed Air Production of the Air Compressor onboard MT Seroja III - Bayhaqi Putra; Nasri; Abdi Seno; Intan Sianturi; Rika Fitriani (Journal of Engineering Science and Technology Management, 2026)
The air compressor is an essential auxiliary machinery onboard MT Seroja III, playing a critical role in supporting vessel maneuverability, operational safety, and main engine starting readiness. During operations, a critical reduction in compressed air production was encountered, leading to prolonged air reservoir filling times and potential risks during ship maneuvering. This study aims to identify the root causes of decreased compressed air production in the main air compressor onboard MT Seroja III and to formulate corrective and preventive maintenance actions based on onboard observations and Fault Tree Analysis (FTA). This research employs a qualitative descriptive method, utilizing continuous monitoring parameter logs, field inspections, and semi-structured interviews with engine officers over a 12-month sea service period. The diagnostic findings using FTA indicate that the decrease in volumetric efficiency was primarily caused by high-resistance suction filter blockages, severe carbon fouling on suction and delivery valves, and piston ring degradation. Corrective maintenance involving filter purging, valve refacing, and piston ring replacement successfully restored the compressor discharge pressure to 30 bar and reduced the air receiver filling time from 45 minutes to 15 minutes. The study concludes that strict adherence to the vessel's Planned Maintenance System (PMS) is mandatory to guarantee operational safety and prevent compression loss.